English Learning and Innovation Skills in 21st: Implementation of Critical Thinking, Creativity, Communication, and Collaboration - Novia, Fitri; Desti Nurdianti; M Bambang Purwanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This essay looks at how to improve English language learning through the application of critical thinking, creativity, communication, and teamwork abilities. Students are expected to be able to navigate life's obstacles on their own thanks to the skills they have acquired since, among other things, a generation raised in the 21st century that is inundated with